2022
DOI: 10.1097/yct.0000000000000814
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive Therapy for Neuropsychiatric Symptoms due to Major Neurocognitive Disorder

Abstract: ObjectivesNeuropsychiatric symptoms (NPSs) in those with major neurocognitive disorder (MNCD) include the responsive behaviors of agitation and aggression. Electroconvulsive therapy (ECT) has shown some effectiveness based on retrospective studies and one open label prospective study. We hypothesized that ECT will reduce NPSs between baseline and after treatment in those with medication-refractory behaviors.Method/DesignThis Canadian prospective multicenter study included MNCD patients admitted to geriatric ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…Therefore, it is encouraging that, in this issue of the Journal of ECT , Copersino et al 1 report that the antidepressant effect of ECT benefits patients regardless of the presence or absence of baseline cognitive impairments. Chan et al 2 then go further to report that ECT improves neuropsychiatric symptoms in patients with neurocognitive disorders, similar to an earlier report in this Journal 3 . To the extent that cognitive adverse effects are a concern in a particular patient, Miller et al 4 found that high power in the electroencephalogram theta band predicts greater acute cognitive adverse effects from high-dose right unilateral ECT, thus creating an opportunity to monitor the ictal electroencephalogram and accordingly adjust the stimulus dose early in the treatment course.…”
mentioning
confidence: 99%
“…Therefore, it is encouraging that, in this issue of the Journal of ECT , Copersino et al 1 report that the antidepressant effect of ECT benefits patients regardless of the presence or absence of baseline cognitive impairments. Chan et al 2 then go further to report that ECT improves neuropsychiatric symptoms in patients with neurocognitive disorders, similar to an earlier report in this Journal 3 . To the extent that cognitive adverse effects are a concern in a particular patient, Miller et al 4 found that high power in the electroencephalogram theta band predicts greater acute cognitive adverse effects from high-dose right unilateral ECT, thus creating an opportunity to monitor the ictal electroencephalogram and accordingly adjust the stimulus dose early in the treatment course.…”
mentioning
confidence: 99%